Resilience by Design: A Multi-Metric Assessment of Urban Vulnerability across Human-Centric, Built, and Climatic Environment Dimensions - Abdelhady, Karim (AUC Knowledge Fountain, 2026)
Urban resilience and sustainability have emerged as fundamental imperatives in contemporary urban planning, as cities face mounting pressures from climate change, population growth, and increasing socio-economic disparities. Resilient urban systems are not only those that withstand shocks, but also those that ensure the long-term well-being, equity, and functionality of their environments. As such, advancing the capacity to systematically evaluate resilience across spatial and temporal scales is critical to informing adaptive, forward-looking planning strategies. Despite a growing body of research on urban resilience, prevailing approaches remain limited in scope and resolution. Many studies tend to examine resilience through isolated lenses—focusing either on infrastructure, environmental risk, or socio-economic vulnerability—without capturing the interconnected nature of these domains. Moreover, commonly used metrics are often derived from coarse, aggregated datasets that obscure the structural and morphological characteristics of urban form. As a result, current frameworks frequently fail to reflect the lived reality of cities and the ways in which urban fabric, microclimate, and service accessibility intersect to influence resilience outcomes. The objective of this study is to develop and apply a spatially explicit, multidimensional Urban Resilience Index (URI) that integrates human, built, and climatic dimensions in order to capture the layered and interdependent drivers of resilience at the neighborhood scale. Drawing from high-resolution geospatial data, the framework moves beyond conventional top-down indicators to capture the physical logic and environmental performance of the city. It introduces three nested and interrelated composite indices—the Climatic Resilience Index (CRI), Built Resilience Index (BRI), and Human Resilience Index (HRI)—which are synthesized into a comprehensive Urban Resilience Index (URI). At the broadest scale, the CRI captures the influence of local environmental and microclimatic conditions that frame the city's exposure and adaptive capacity. Enveloped within this context, the BRI assesses the structural and spatial logic of the built environment—its form, configuration, and connectivity—as the mediating layer through which climate is filtered and resilience is materially embedded. At the core lies the HRI, which reflects how effectively urban environments translate physical and environmental conditions into equitable, livable, and supportive spaces for human life. Together, these indices form a layered understanding of urban resilience—one that acknowledges the foundational role of climate, the structuring force of built form, and the ultimate goal of human well-being. Through spatial clustering and comparative analysis, the framework reveals distinctive resilience profiles across the city, highlighting zones of both vulnerability and strength. The results demonstrate that resilience is not uniformly distributed and that trade-offs often emerge between dimensions—for instance, areas exhibiting environmental robustness may lack connectivity or morphological efficiency, while zones designed for accessibility may be more exposed to climatic stressors. These findings underscore the necessity of integrated, place-specific strategies that account for the complexity of urban systems rather than relying on generalized or siloed approaches. By bridging disciplinary boundaries and embedding resilience within the spatial structure of the city, the proposed framework offers a robust foundation for evidence-based planning. It advances the discourse on resilience from abstract principles to operational tools, enabling more responsive, equitable, and climate-conscious urban futures.